KAP on antibiotic usage and resistance among second professional medical students - Khajuria, Kanika; Kaur, Sharminder; Sadiq, Shamiya; Khajuria, Vijay (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Antibiotics are wonder drugs as they prevent and treat bacterial infections. However, their irrational use even by wrong prescribing behaviour of physician leads to antibiotic resistance medical students are future doctors and are provided knowledge and practice of antibiotics in treatment, and prevention of diseases in their study curriculum of second professional course mainly in chapters of pharmacology and microbiology. Therefore, the present study was to determine the second-year medical students’ knowledge, attitude and perception regarding antimicrobial use and resistance. Methods: Study was conducted on second professional undergraduate medical students from Government Medical College, Jammu. 140 students participated, and informed consent was taken prior to study. A validated questionnaire comprised of 20 questions was provided to them and responses were recorded. Questionnaire was comprised of 20 questions (13 questions attributed to knowledge of antibiotics usage and resistance, six to attitude and one question regarding perception). Results: The students showed fair knowledge about antibiotics and resistance. Percentages of fully correct answers was between 63-100% regarding knowledge of antibiotics. The attitude results revealed that self-medication by the student was observed in 67%, while 70% agreed that they had left over antibiotics at home, but only 42% committed that they take these left over antibiotics. As far as practice was concerned the maximum students consult text books as source of knowledge regarding resistance followed by Wikipedia. Conclusions: The current study observed high score of knowledge than attitude in medical students regarding antibiotic usage and resistance and increasing influence of internet like Wikipedia. This underscores the need for more effort in updating the students regarding antibiotic usage and resistance and laying more emphasis in the core curriculum of their academics.